Efficiency of basketball point guard player in games - Popescu, F.; Porfireanu, M.-C.; Ristea, C. (Journal of Sport and Kinetic Movement, 2019)
Modern sports games training methodology has some important changes in the conception of content, structure and organization of the players` training. Each sport game has a modeling method applicable, as well as in basketball training. In a basketball team, each player has a specific position on court, but the players are request to play more positions (roles) in a game. So, that means the players have to be able to change fast their role in order to win points. Material and methods Goal`s paper is to analyze the efficiency of the actions of the leading basketball player in 2017 National Championship in Romania. The hypothesis: if the individualized basketball training the coach` aims are increasing the effectiveness of the attack actions, then on the official games, the leader will have high percentages in the playing model. The research methods used are: scientific documentation, case study, statistical-mathematical method, graphic method. The study was based on the record sheets of 35 official games from Women's Basketball National Championship in a competitive year, 2017. Results: We analyzed the point guard` efficiency in the basketball team performance. We recorded the game model indicators for the female Romanian basketball team. Discussions and conclusions One of the most important role of the players is to be point guard. For this, the player has to be very good in handling the ball, for passing, dribbling, throwing, shooting. The most important action of the point guard player is to initiate offensive play.